4A Zeolite Support for Pt Nanoparticles towards Methanol Oxidation. Issue 10 (28th May 2019) - Cai, Nan; Wu, Jialu; Jin, Changchun
Abstract : The effect of 4A zeolite as a support on the electrocatalytic activity of Pt nanoparticles for the oxidation of methanol has been investigated. Pt/4A zeolite and Pt/C catalysts with the same mass of Pt are prepared by loading the Pt nanoparticles stabilized by PEG-400 on 4A zeolite and carbon black, respectively. Physical analyses reveal unevenly distributed but no large agglomerates of the Pt nanoparticles on the surface of 4A zeolite due to PEG-400 attached to the Pt nanoparticles, while the Pt nanoparticles on carbon black show a uniform distribution and a lesser degree of agglomeration. However, Pt/4A zeolite shows a much more negative onset potential and a significantly higher peak current density than Pt/C in methanol oxidation in both acidic and alkaline solutions. Pt/4A zeolite also shows high resistance to the poisoning caused by CO-like species formed in the reaction. The results indicate that 4A zeolite is superior to carbon black as a support for the Pt nanoparticles toward methanol oxidation, and further suggest that some types of zeolites could be used as efficient support materials in electrocatalysis.